Viator per devia scientiae itinera. Studia nad problematyką okresów przedrzymskiego, rzymskiego, wędrówek ludów i wczesnego Średniowiecza - Redakcja (Wydawnictwo Naukowe UAM, 2016)
Viator per devia scientiae itinera is dedicated to prof. dr hab. Tadeusz Makiewicz in honour of His 70th birthday. The book’s title aptly describes Professor Makiewicz’s engagement with archaeology: wandering through devious paths of archaeological wilderness, Professor often contested predominant schemes, introducing invigorating trends into the study of the whole range of issues concerning the closing centuries of the past era and the early days of the new one. This volume comprises two complementary parts. Miscellanea present the biography and research activities of Professor Makiewicz as well as the memoirs of the friends of his youth. In the core of the volume, Studia, a number of researchers provide their own constructive input into the development of research problems devotedly studied by Professor Makiewicz. The papers provide a record of the scholarly journeys of their authors, who pursued the paths set by Professor. This part of the book explores such issues as all kinds of changes in the funeral sphere, studies of settlement sites and pottery. In addition, the papers aim to provide insights into the world of human values and seek to re-read archaeological record, a problem so dear to Professor Makiewicz’s heart. The volume begins with the complete bibliography of Professor Tadeusz Makiewicz’s works, providing a guide for the pathways Professor Makiewicz followed in his scholarly journey through the wilderness of knowledge.

Studia ofiarowane prof. dr. hab. Tadeuszowi Makiewiczowi w jego siedemdziesiąte urodziny stanowią wkład ofiarowujących mu je autorów w dalszy rozwój tych problemów badawczych, którym swą naukową karierę poświęcił profesor Tadeusz Makiewicz. Profesor Tadeusz Makiewicz jest wychowankiem Katedry Archeologii Uniwersytetu Łódzkiego. Swą karierę zawodową złączył z Uniwersytetem im. Adama Mickiewicza w Poznaniu. Był Prodziekanem Wydziału Historycznego, wieloletnim Wicedyrektorem i Dyrektorem Instytutu Prahistorii UAM, był także przez lata swojej niezwykle aktywnej pracy zawodowej animatorem zainteresowań okresem przedrzymskim i wpływów rzymskich dla licznego grona adeptów archeologii naszej uczelni. Głównymi kwestiami niniejszego tomu są zagadnienia religioznawcze, etniczne oraz studia nad osadami i wytwórczością ceramiki szeroko pojętych okresów: przedrzymskiego, wpływów rzymskich oraz wędrówek ludów, takoż przełomu starożytności i wczesnego średniowiecza, a zatem zagadnienia dominujące w niezwykle szerokim spektrum badawczym Profesora.
Viator per devia scientiae itinera. Studies in the Pre-Roman Iron Age, the Roman Iron Age, the Migration Period and the Early Middle Ages
Keywords: okres przedrzymski; okres rzymski; wędrówki ludów; starożytność; średniowiecze; Tadeusz Makiewicz